Core muscle activation during Pilates exercises on the Wunda chair - Panhan, Ana C.; Gonçalves, Mauro [UNESP]; Eltz, Giovana D. [UNESP]; Villalba, Marina M. [UNESP]; Cardozo, Adalgiso C. [UNESP]; Bérzin, Fausto (Elsevier, 2021)
Objetives: The Pilates method, developed by Joseph Pilates (1886–1967), has been widely used to improve trunk stability, muscle flexibility and strength, physical fitness, and body awareness. To measure the electromyography of four trunk muscles during three Pilates exercises carried out of the wunda chair. Desing: cross-section study. Methods: Sixteen women participated in this study with a height and body weight of 1.64 ± 0.04 m and 58.7 ± 7.4 kg, respectively, and a mean age of 27.6 ± 3.7 years. Rectus abdominis (RA), internal oblique (IO), longissimus (LO), and multifidus (MU) muscles was evaluated by electromyographic (EMG) tests activity during three Pilates exercises: going up front (GF), mountain climb (MC), and swan (SW). EMG was normalized and expressed in the time domain, by the RMS. Results: The highest EMG values concerning the four muscles were observed for the MC exercise, followed by GF and SW (ANOVA: p = 0.0001, p = 0.04, p = 0.0002, and p = 0.0013, respectively). Our results show that the three Pilates exercises could recruit all the muscles, with a moderate activity intensity. The ANOVA; p < 0.05 showed significant difference between the muscles, concerning SW (p = 0.0002). Conclusion: Our results show that the three Pilates exercises could recruit all the muscles, with a moderate activity intensity.
Keywords: Biomechanics; Core; EMG; Pilates; Trunk